Mirabegron for medical expulsive therapy of ureteral stones: a systematic review and meta-analysis - Song, Haifeng; Liang, Lei; Liu, Hui; Liu, Yubao; Hu, Weiguo; Zhang, Gang; Xiao, Bo; Fu, Meng; Li, Jianxing (Frontiers in Medicine, 2024)
Objective: To systematically review and quantitively evaluate the efficacy and safety of mirabegron as a medical expulsive therapy for ureteral stones.We performed an extensive search of the EMBASE and PubMed databases for studies examining the use of mirabegron as a medical expulsive therapy for ureteral stones. The primary outcome measure assessed was the stone expulsion rate (SER), while the secondary outcomes evaluated were the stone expulsion interval (SEI) and the occurrence of pain episodes during follow-up. Risk ratios (RRs) and mean differences (MDs) with their respective 95% CIs were calculated.We included a total of seven studies involving 728 participants. Our analysis revealed a significant increase in the stone expulsion rate (SER) with mirabegron (RR=1.40; 95% CI=1.17-1.67; P < 0.001) and a reduction in the frequency of pain episodes (MD=-0.80; 95% CI=-0.39 to -0.21; P=0.008) compared to the control group.No significant difference was found in SEI between the two groups (MD=-3.04; 95% CI= -6.33 to 0.25; P=0.07). Subgroup analysis revealed that the increased SER was significant for distal ureteral stones, but not for proximal and middle ureter stones.Compared to tamsulosin or silodosin, mirabegron showed no significant difference in SER, SEI, or pain episode frequency. The adverse effects of mirabegron were relatively rare and mild.Mirabegron appears to be a promising candidate for the MET of distal ureteral stones rather than proximal and middle ureteral stones, as it significantly increases SER and reduces pain episode frequency. Further well-designed randomised controlled trials are needed to validate and affirm these findings.